Energy and exergy analysis of co-gasification of crude glycerol and animal fat mixtures. (1st April 2022) - Almeida, Ana; Pilão, Rosa; Ramalho, Elisa; Pinho, Carlos
This work presents an energy and exergy analysis of co-gasification tests of crude glycerol and animal fat mixtures, in order to obtain first and second law efficiencies, the last ones representing a novelty in the field of gasification technology. Mixtures with 5% (w/w) of dry animal fat, 57% (w/w) of dry treated crude glycerol and 38% (w/w) of water were studied in a fixed bed down flow gasification reactor at 800°C and 900°C. The increase of gasification temperature seems not to affect the energy and exergy yields of the overall process.